Effects of operative conditions on membrane fouling of jet loop membrane bioreactor - 徐高田 孙佳琳 秦哲 阮慧娟 (Journal of Shanghai University, 2010)
The orthogonal experiments, which involves three factors： aeration intensity, suction time and suction suspended time, were designed to research membrane fouling of jet loop membrane bioreactor （JLMBR）. Experimental results indicate that increasing aeration intensity, reducing suction time and increasing suction suspended time all could mitigate membrane fouling effectively. However excessive aeration intensity, too short suction time and excessive suction suspended time were bad for bioreactor running. The optimal aeration intensity, suction time and suction suspended time were 0.75 1.00 m3/（m2.h）, 8 -10 min and 4 -5 min, respectively. The three factors all had effect on membrane pollution rate, while the suction time was the most important one and followed by aeration intensity and suction suspended time. It also indicates that, comparing with traditional submerged membrane bioreactors, JLMBR had lower membrane pollution rate.